AUGMENTED RENAL CLEARANCE IMPLIES A NEED FOR INCREASED AMOXICILLIN-CLAVULANATE DOSING IN CRITICALLY ILL CHILDREN. Issue 1 (14th December 2015) - Cock, Pieter De; Standing, Joseph; Barker, Charlotte; de Jaeger, Annick; Carlier, Mieke; Dhont, Evelyn; Verstraete, Alain; Delanghe, Joris; Robays, Hugo; Paepe, Peter De
Abstract : Background: Amoxicillin/clavulanate is commonly used to treat community-acquired infections on the pediatric intensive care unit. Few data are available to guide dosing in this vulnerable population. Methods: This prospective pharmacokinetic study enrolled patients admitted to the pediatric intensive care unit in whom intravenous amoxicillin-clavulanate was indicated (25–35 mg/kg q6h). Serial blood samples were obtained following the first and steady-state doses and amoxicillin/clavulanate concentrations were measured by a validated high-pressure liquid chromatography (HPLC)-tandem mass spectrometry method. Population pharmacokinetic analysis and Monte Carlo simulations were conducted using NONMEM' 7.3. Results: Three hundred twenty-five amoxicillin and 151 clavulanate blood samples were collected from 50 patients with a median age of 2.58 years (range: 0.08–15 years). A 3-compartment model for amoxicillin and a two-compartment model for clavulanate best described the data, in which allometric weight scaling and maturation functions were added a priori to scale for size and age. In addition, serum Cystatin C (sCysC) 'as a marker for renal function' and concomitant treatment with vasopressors were identified to have a significant influence on amoxicillin clearance. The typical population values of clearance for amoxicillin and clavulanate were 17.97 L/H/70 kg (95% CI:15.33–21.30 L/H/70 kg) and 12.20 L/H/70 kg (95% CI:10.54–14.55 L/H/70 kg), respectively. Four hourly dosing of 25 mg/kg (based on the amoxicillin component) was required to achieve 40% of the dosing interval for amoxicillin concentrations to be above MIC, and for clavulanate levels to be maintained above 2 mg/L. For patients with augmented renal function a 1 hour infusion was preferable to bolus dosing to achieve the therapeutic target. Conclusions: Current dosing regimens result in subtherapeutic concentrations in the early period of sepsis due to augmented renal clearance, which risks treatment failure in critically ill children.